Thermal Stress Concentration in Plates from Different Materials - (:unkn) unknown (AMER INST AERONAUTICS ASTRONAUTICS, 2012)
Manufacturing of welded plates with different materials are widely employed in industrial application that is exposed to mechanical and temperature loads. In this study, thermal stress distribution in plates from different materials containing a defect, a rectangular hole with semicircular caps, near a joining line is numerically investigated under the homogeneous change of temperature. Investigations are carried out for the cases of butt and bevel-joint welds for different locations of the hole. Maximum of stress concentration factor is encountered when the longitudinal-axis of the hole is at an angle of 45 deg to the joining line in the case of butt-joint weld. Variation of the tangential stress component of the hole-tip has a jump when it crosses over the joining line. The stress intensity factors in considered structures are determined using the obtained results of stress concentration factors for variations of radius of hole-caps. An expression is proposed to obtain the stress in the bevel-joint using values in the butt-joint plate. For a comparison, thermal stresses are also investigated in a model made from an optical sensitive material using the method of mechanical modeling of photothermoelasticity for a butt-joint plate. The comparison shows the agreement between numerical and experimental solutions.
Keywords: INTENSITY FACTOR; CRACK; INTERFACE